A benchmark specimen of Muiscasaurus catheti from the upper Aptian of Villa de Leiva, Colombia: New anatomical features and phylogenetic implications. (March 2021) - Páramo-Fonseca, María Eurídice; García-Guerrero, Javier; Benavides-Cabra, Cristian David; Padilla-Bernal, Santiago; Castañeda-Gómez, Antonio José
Abstract: A new specimen of Muiscasaurus catheti Maxwell et al., 2016 from upper Aptian of the Paja Formation found in Villa de Leiva (Boyacá, Colombia) is described herein. It consists of a well preserved skull and a nearly complete axial skeleton of a sub-adult individual and provides valuable new morphological information on the species, including two autapomorphies: the presence of a quadratojugal with extremely reduced external exposure, and basioccipital floor of the foramen magnum with a medially furrowed anterior ridge. A detailed comparison between the new specimen (FCG-CBP-16) and the holotype (CIP-FCG-CBP-74) allows us to reinterpret some features of the original description of M. catheti that were obscured by the highly deformed and partially unprepared state of the holotype. Consequently, we propose the new specimen (FCG-CBP-16) to be a benchmark specimen for the species. Morphological comparisons with other Ophthalmosauridae highlight the affinities between M. catheti and the species of the Upper Jurassic genus Ophthalmosaurus . A phylogenetic analysis recovers M. catheti in a 'basal' position within Ophthalmosaurinae, supporting its proximity to Ophthalmosaurus and contrasting with previous topologies where M. catheti was recovered as a basal Platypterygiinae. This implies a temporal extension of the Ophthalmosaurinae up to the Aptian in South America. Highlights: A benchmark specimen for the species Muiscasaurus catheti is described. Two new autapomorphies of the M. catheti are identified. New morphological features of M. catheti are revealed. M. catheti is recovered within Ophthalmosaurinae. . The Ophthalmosaurines are now recorded up to the Aptian in South America.